1996
DOI: 10.1080/02701367.1996.10607963
|View full text |Cite
|
Sign up to set email alerts
|

On the Interaction of Concurrent Verbal and Manual Tasks: Which Initial Task Conditions Produce Interference?

Abstract: The presence of interference (and whether it is generalized or lateralized) is highly dependent on the initial conditions of the experiment. Changes in task, instructions, and subject characteristics produce different interference outcomes. Clearly the present results are not predictable from the cerebral functional distance theory and support the idea that the theory has limited explanatory power depending on the specific tasks and conditions involved. Alternatively, the idea of entrainment among tasks can ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…If anything, participants in the Meaningless Movement condition showed a benefit on one measure of lexical access (non-juncture filled pauses) relative to Meaningful Movement and No Movement, but without a concurrent benefit on working memory performance. This finding is consistent with reports that movement can facilitate lexical access and fluency (Chang & Hammond, 1987; Pellecchia, Shockley, & Turvey, 2005; Ravizza, 2003; Treffner & Peter, 2002; Whitall, 1996). Importantly, however, lexical access and verbal production were not enough to explain the working memory benefit associated with gesturing in our study, suggesting that movement may work differently to facilitate working memory than it works to support verbal production.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…If anything, participants in the Meaningless Movement condition showed a benefit on one measure of lexical access (non-juncture filled pauses) relative to Meaningful Movement and No Movement, but without a concurrent benefit on working memory performance. This finding is consistent with reports that movement can facilitate lexical access and fluency (Chang & Hammond, 1987; Pellecchia, Shockley, & Turvey, 2005; Ravizza, 2003; Treffner & Peter, 2002; Whitall, 1996). Importantly, however, lexical access and verbal production were not enough to explain the working memory benefit associated with gesturing in our study, suggesting that movement may work differently to facilitate working memory than it works to support verbal production.…”
Section: Discussionsupporting
confidence: 93%
“…McNeill, 1992), rather than its properties as a vehicle for conveying meaning. In fact, moving one’s hand in meaningless ways has been shown to facilitate speaking, particularly when the timing of the movement and the speech are synchronized (Chang & Hammond, 1987; Pellecchia, Shockley, & Turvey, 2005; Ravizza, 2003; Treffner & Peter, 2002; Whitall, 1996). For example, Chang and Hammond (1987) found that speech rate increased to synchronize with the rate of the speaker’s cyclical finger movements.…”
mentioning
confidence: 99%
“…The results of our study can also be attributed to differences in processing loads of the stimuli. That is, unlike music the speech stimuli must have maintained a higher degree of memory load [ 12 ] and attention load [ 11 ]. This acted as interference during swallowing.…”
Section: Discussionmentioning
confidence: 99%
“…They include capacity sharing, cross-talk, and bottleneck. The capacity sharing postulates that reduced performance in the dual task is due to shared neural substrates for a function [ 10 ] leading to competition between the tasks whereas the cross-talk deals with decreased performance in tasks due to sharing of similar processing units like attention [ 11 ] and memory [ 12 ]. Lastly the bottleneck effect reviews reduced performance due to bottleneck resulting from the competition for the same information processing [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, when the concurrent speech-hand task is performed using the left hand, given that the left hand is primarily controlled by the right hemisphere while speech is primarily controlled by the left hemisphere, it has been argued that, the two activities may proceed in parallel with a lesser effect of speech on the performance of the left hand (Kinsbourne & Hicks, 1978). However, a functional bidirectional coupling between speech and finger movement has been observed suggesting that the interaction between concurrently active effectors might better be viewed as coordination rather than interference (Chang & Hammond, 1987;Kelso, Tuller, & Harris, 1983;Whitall, 1996). A further advantage of a dynamics perspective on inter-effector coupling is that it can encompass non-intentional movements such as the vegetative processes underlying the coordination of respiration and locomotion (Amazeen, Amazeen, & Beek, 2001;Goldfield, Schmidt, & Fitzpatrick, 1999), as well as a wide range of phenomena involving the coordination of perception and action (Treffner & Morrison, 2001).…”
Section: Introductionmentioning
confidence: 99%